The Restorative Justice Model that Combines the Criminal Procedure Code and Living Laws in the Community in the Melayu Asahan Community, North Sumatra. - Azmiati Zuliah (Faculty of Law, Universitas Pekalongan, 2023)
The resolution of cases involving children in conflict with the law in Indonesia still lacks a clear concept regarding the application model of diversion and the living law in society. This study is significant considering the numerous restorative justice models based on living law in society that have not been accommodated in Indonesian legislation. This research aims to understand, analyze, and describe: (1) the regulation of restorative justice in resolving criminal acts by Children in Conflict with the Law in Indonesia through diversion; (2) the concept of restorative justice in the practice of local wisdom of the Malay Asahan cultural community; and (3) a model of combining RJ application according to the provisions of the Juvenile Justice Law. The study found that the Malay Asahan community, which includes the City of Tanjungbalai, Asahan Regency, and Batubara Regency, still practices